Pra-Rancangan Instalasi Pengolahaan Lindi di Tempat Pemprosesan Akhir (TPA) Nangkaleah Kecamatan Wangunreja, Kabupaten Tasikmalaya - Salman, Nurcholis; Ningsih, Nuraeni Cahyati; Aryanti, Dini (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2020)
A fire disaster that occurred at the Cinangsi sanitary landfill in 2015 leads the Nangkaleah sanitary landfill in Wangunreja, Tasikmalaya must be operated earlier, even though the Nangkaleah landfill has not been equipped with several final processing facilities, including a leachate processing unit. The initial design of the leachate treatment unit at the Nangkaleah landfill is considered to be much smaller than the total leachate generation from waste imported from the Cinangsi's service area and the planned Nangkaleah's landfill service area. Thus, it is necessary to design a leachate treatment facility that has a much larger capacity. The purpose of this study is to plan the design of leachate treatment units based on projections of waste generation from 2 (two) service areas, rainfall data, and projections of leachate generation. The results of this study indicate that the projected discharge of leachate at Nangkaleah landfill is 0.94 m3/day. The leachate processing facility that is planned consists of 2 (two) units of leachate storage ponds with a capacity of 40 m3 each, a stabilization pool with a capacity of 20 m3, an aeration pool with a capacity of 20 m3, a maturation pool with a capacity of 15 m3, a leachate recirculation system and wetland area. The facility is considered capable of reducing levels of leachate pollutants to meet environmental quality standards